Prevalence of anemia and factors affecting its management strategies among children below five years at Mityana general hospital, Mityana district. A cross sectional study. - Kabunga Ibrahim (Student's Journal of Health Research, 2022)
Background Anemia is a public health concern in the world affecting both developing and developed countries. It is one of the major causes of death among children under five years in Africa, with a prevalence of 64.6% among preschool children. (BMC Pediatrics, 2017) Methodology This was a cross-sectional study that involved health workers attending to children admitted to the Paediatric ward at MGH. The sample size was 85 health workers, it was determined using the Kish and Leslie formula. Data were analyzed using tables and pie charts. It was conducted to assess the prevalence of anemia and factors affecting its management strategies among children below five years at MGH, Mityana district. Results Study findings revealed that anemia is one of the commonest conditions encountered in the pediatric ward with 20-30 children with anemia being admitted to the pediatric ward on a daily basis. 45, (53%) reported that 20-30 children with anemia are admitted on a daily basis.75 (88%) reported that 10-20 children report anemia as a complication on a daily basis. 65(76%) reported that 10-20 children present with complications as a result of long-standing anemia on a daily basis, Majority of health workers, 72 (85%) reported the use of a holistic/multidisciplinary approach in the management of anemia. Conclusion Anemia was found to be highly prevalent in children admitted to the ward, respondents managed anemia mostly with blood transfusion and oral ferrous sulfate. It was also found that they didn't have enough drugs to aid in the management of anemia in children below five years. Recommendations The researcher recommends Continuous Support supervision by health professionals to improve the management of anemia in children below five years and a Frequently monitored supply of drugs in government facilities by the MOH.